Perforating Fibrous Histiocytoma Mimicking Keratoacanthoma: A Case Report - Alina Lungu; Aurélie Hsieh; Gürkan Kaya; Sébastien Menzinger (MDPI AG, 2023)
A 31-year-old male presented with a firm, well-demarcated, erythematous, crateriform, and ulcerated nodule in the left lumbar region, which persisted for 3 months. Clinically, a keratoacanthoma was suspected. The histological analysis was consistent with perforating fibrous histiocytoma, a rare histopathologic variant of fibrous histiocytoma. To our knowledge, this is the third case reported in the literature.